2023
DOI: 10.3389/fonc.2023.1164391
|View full text |Cite
|
Sign up to set email alerts
|

An ileal gastrointestinal stromal tumor misdiagnosed as pelvic metastases from rectal cancer: a case report

Abstract: With the advancement of imaging and pathological diagnostic methods, it is not uncommon to see synchronous gastrointestinal stromal tumors (GIST) and other primary cancers, the most common of which are synchronous gastric cancer and gastric GIST. However, synchronous advanced rectal cancer and high-risk GIST in the terminal ileum are extremely rare, and they are easily misdiagnosed as rectal cancer with pelvic metastases due to their special location near iliac vessels. Herein, we report a 55-year-old Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…One case report demonstrated that apatinib monotherapy can induce partial response in synchronous GIST and primary gastric adenocarcinoma following the progression of both tumors on a combination of imatinib and S1 (oral fluoropyrimidine) therapy [ 7 ]. In another case, adjuvant CAPOX + 400 mg imatinib showed efficacy in limiting the progression of disease in synchronous rectal cancer and GIST [ 15 ]. In the present case, we had to perform treatment of a synchronous duodenal adenocarcinoma and GIST metastatic to the peritoneum in a patient who had already failed FOLFOX and mFOLFIRI therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One case report demonstrated that apatinib monotherapy can induce partial response in synchronous GIST and primary gastric adenocarcinoma following the progression of both tumors on a combination of imatinib and S1 (oral fluoropyrimidine) therapy [ 7 ]. In another case, adjuvant CAPOX + 400 mg imatinib showed efficacy in limiting the progression of disease in synchronous rectal cancer and GIST [ 15 ]. In the present case, we had to perform treatment of a synchronous duodenal adenocarcinoma and GIST metastatic to the peritoneum in a patient who had already failed FOLFOX and mFOLFIRI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited data exists outlining proper procedure in cases of an inoperable primary GI malignancy and a concurrent inoperable metastatic GIST. First-line medical therapy for small bowel adenocarcinoma is typically oxaliplatin-based regimens such as capecitabine plus oxaliplatin (CAPOX) or leucovorin, 5-fluorouracil, oxaliplatin (FOLFOX) [ 15 ]; however, most patients with GIST are treated with imatinib or other tyrosine kinase inhibitors (TKIs) [ 15 , 16 ]. Concurrent treatment has largely been avoided in previous studies due to risks of severe neutropenia on a combined regimen of a TKI and standard chemotherapy regimens [ 15 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation